Evaluasi Sistem Informasi Manajemen Puskesmas Guna Mendukung Penerapan Sikda Generik Menggunakan Metode Hot Fit Di Kabupaten Purworejo - Viera Juniver Thenu; Eko Sediyono; Cahya Tri Purnami (Jurnal Manajemen Kesehatan Indonesia, 2016)
Purworejo District Health Office (DHO) has developed Health Center Management Information System (HCMIS) to provide quick, precise, and accurate information for supporting the process of decision making and the policy of services at Health Center. However, there was still any empty forms and did not use the system. To standardize Health Information System, Ministry of Health has released a concept of Generic SIKDA. Therefore, the system applied by Purworejo DHO needs to be evaluated using the method of HOT fit. This was qualitative research using indepth interview and direct observation. Main informants were nine data operators and informants for triangulation purpose was six persons from health centers and five persons from DHO. Furthermore, data were analyzed using content analysis. The result of this research revealed that the application of HCMIS at Purworejo DHO was equal to Generic SIKDA. The system had been applied routinely but there was no a guidance book and training. Number of human resources was sufficient. However, there needed to make an implementer team of Health Information System in accordance with competency. There was no routine monitoring and current budget was not sufficient to maintain hardware to support the system. Quality of the system used was good, easy to use, and available of menu to communicate data. Unfortunately, quality of resulted information had still been inaccurate and incomplete because it did not cover data of services at Subsidiary Health Centers (SHC) and Village Health Posts (VHP). The lateness of services was related to a funding procedure. HCMIS at Purworejo DHO was equal to Generic SIKDA but it had not been used to make a decision. As a suggestion, DHO needs to conduct training, monitor, and provide hardware and a network. Meanwhile, Health Centers needs to make a commitment for applying the HCMIS maximally by SHC and VHP.